Nomenklatur Program Studi Hukum Keluarga Islam dan Persepsi Masyarakat: Studi Empiris di Kabupaten Rejang Lebong - Laras Shesa; Elkhairati; Gita Olviyani; Liddia Febi Agustin (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2026)
Changes in the nomenclature of the Islamic Family Law Study Programme (HKI) at State Islamic Religious Universities are often assumed to affect the level of public understanding and interest in the study programme. This study aims to analyse public perceptions of the naming of the Islamic Family Law Study Programme and its implications for study interest in Rejang Lebong Regency. This study uses a descriptive quantitative approach with a survey method. Data were collected through questionnaires administered to 439 respondents from various social backgrounds and regions. The results show that the public's understanding of the name of the Islamic Family Law Study Program is moderate, with the majority of respondents aware of the existence and general characteristics of the study program, although they do not yet have a comprehensive understanding of the competencies of graduates and their career prospects. Empirical findings also show that the name of the study program does not have a significant effect on the decline in the number of new students, as evidenced by the stability and even increase in the number of applicants in the last academic year. This study concludes that the main factor influencing student interest is not the nomenclature of the study programme, but rather strategies to strengthen its academic image and socialise graduate competencies. Therefore, strengthening the brand image of the Islamic Family Law Study Programme is a strategic step in increasing its competitiveness and public trust.